Dosing Regimen of Enrofloxacin Impacts Intestinal Pharmacokinetics and the Fecal Microbiota in Steers - Ferguson, Kaitlyn M.; Jacob, Megan E.; Theriot, Casey M.; Callahan, Benjamin J.; Prange, Timo; Papich, Mark G.; Foster, Derek M. (Frontiers in Microbiology, 2018)
Objective: The intestinal concentrations of antimicrobial drugs that select for resistance in fecal bacteria of cattle are poorly understood. Our objective was to associate active drug concentrations in the intestine of steers with changes in the resistance profile and composition of the fecal microbiome. Methods: Steers were administered either a single high dose (12.5 mg/kg) or multiple 3 low dosemultiple doses (5 mg/kg) of enrofloxacin subcutaneously every 24 hours. Enrofloxacin and ciprofloxacin concentrations in intestinal fluid were measured over time96 hours, as andwere the abundance and resistance MIC of E. coli in culture and the composition of the fecal microbiota by 16S rRNA gene sequencing were assessed over 192 hours after initial treatment. Results: Active drug concentrations in the ileum and colon exceeded plasma and interstitial fluid concentrations, but were largely eliminated by 48 hours after the last dose. The concentration of E. coli in the feces significantly decreased during peak drug concentrations, but returned to baseline by 96 hours in both groups. The median MIC of E. coli isolates increased for 24 hours in the high dosesingle dose group, and for 48 hours in the low dosemultiple dose group. The median MIC was higher in the low dosemultiple dose group when compared to the high dosesingle dose group starting 12 hours post-treatmentafter the initial dose. The diversity of the fecal microbiota did not change in either treatment group, and taxa-specific changes were primarily seen in phyla commonly associated with the rumen. Conclusions: Both dosing regimens of enrofloxacin achieve high concentrations in the intestinal lumen, and the rapid elimination mitigates long-term impacts on fecal E. coli resistance and the microbiota.